PhotoScreenerTM for preschool children visual screening - Lavezzo,Marcelo Mendes (2010)
PURPOSE: To evaluate whether the PhotoScreenerTM (PS) is useful as a method of screening in the prevention of amblyopia in children. METHODS: 227 preschool children were evaluated through the application of a questionnaire, refratometry measurements and photos using the PS. After this, all children were submitted to cycloplegic refraction, 30 minutes after one drop of cycloplegic agent. Refraction was performed by a mydriatic automatic refractor Shin Nippon®. Children identified as suffering from eye problems were treated, according to the criteria: hyperopia greater than +1.50 D, myopia greater than -1.00 D and astigmatism greater than 1.00 D. Data were analyzed through Goodman test, descriptive statistics and study of the specificity and sensitivity of the use of PS, comparing its results with other ophthalmologic assessment methods. RESULTS: There was a male predominance (54.6%), and the majority of children were four or five years old. PS sensitivity (S) compared to refraction under cycloplegia was 50.9%. The specificity (E) was 78.9%, positive predictive value (PPV) = 70%, negative predictive value (NPV) = 62.5% and accuracy (A) = 65.1%. CONCLUSIONS: PS, when compared to cycloplegic refraction spherical equivalent, is a reasonable method of screening, although the low sensitivity. A positive point to be emphasized is the considerable specificity.